Soul trader : putting the heart back into your business - Ogunlaru, Rasheed, 1970- (Kogan Page, 2012)
If your heart's not in your business, why are you? In the flurry of everyday deadlines, fire fighting and all the pressing demands on our time, it's easy to forget the real reasons we started our own business in the first place. Soul Trader helps you connect with your personal mission, values and passion to create a 'stand out from the crowd' business that enriches you both financially and emotionally. Discover the seven essential principles that will help you build a business sensitive to today's economic and social realities, one that is profitable, customer-focused and in tune with your own.